2017
DOI: 10.1080/21678421.2017.1338298
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of telehealth into a multidisciplinary ALS Clinic: feasibility and acceptability

Abstract: Telehealth was generally viewed favourably by ALS patients, caregivers, and multidisciplinary team members. Improvements in technology and in methods to provide satisfactory remote care without person-to-person contact should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 25 publications
3
97
0
1
Order By: Relevance
“…For patients requiring a longer discussion with the palliative care specialist, we are piloting the option of a palliative care video televisit on a separate date. This has been successfully utilized at our center and others as a means of maintaining care continuity …”
Section: Discussionmentioning
confidence: 99%
“…For patients requiring a longer discussion with the palliative care specialist, we are piloting the option of a palliative care video televisit on a separate date. This has been successfully utilized at our center and others as a means of maintaining care continuity …”
Section: Discussionmentioning
confidence: 99%
“…High levels of patient acceptance and satisfaction with telehealth services have been reported, while one study noted patients expressed preference for face‐to‐face visits for discussions of more sensitive psychosocial topics . A recent study by Geronimo and colleagues found high levels of patient satisfaction with video teleconferencing in lieu of face to face visits among persons with ALS . Telehealth monitoring of noninvasive ventilatory support has been associated with decreased emergency room visits and hospital admissions .…”
Section: Specific Telehealth Applications For Neuromuscular or Musculmentioning
confidence: 99%
“…Similar reasons were expressed by our cohort, although with lesser frequency. Travel and time factors may be resolved by use of telehealth which has been utilised with success in MND …”
Section: Discussionmentioning
confidence: 99%
“…Travel and time factors may be resolved by use of telehealth which has been utilised with success in MND. 9 Transition from paediatric to adult services has been associated with deterioration in health and highlights the potential for disintegration of care for patients with NMD. Many transfer from a networked paediatric team to fragmented adult care.…”
Section: Brief Communicationsmentioning
confidence: 99%